Bi(OTf)3‐catalyed One‐pot Synthesis of α‐Halo‐β‐amino Ketones and Acyl Aziridines from 3‐Aryl Propargyl Alcohols. Issue 13 (1st June 2021) - Zhang, Qinglin; Duan, Yongbin; Guo, Huifeng; Yang, Hong; Zhai, Jiulong; Li, Tiantian; Wang, Zhihai; Lu, Xiaolei; Wang, Yan; Yin, Yan
Abstract: A Bi(OTf)3 ‐catalyed reaction of 3‐aryl propargyl alcohols with sulfonamide and halogen source was firstly investigated, which provided a facile route for the synthesis of a large variety of α‐halo‐β‐amino ketones. The key intermediates, β‐amino ketones, were obtained through tandem Meyer‐Schuster rearrangement reaction of propargyl alcohols and intermolecular Michael addition of α, β‐unsaturated ketones and sulfonamide. Then the in situ generated α‐halo‐β‐amino ketones underwent the base‐promoted intramolecular cyclization to give diverse acyl aziridines in a one‐pot fashion. These transformations are reliable on a large scale. The high yields and convenient experimental operations make it a valuable method for the construction of α‐halo‐β‐amino ketones and acyl aziridine derivatives. Abstract : A synthetic route to construct α‐halo‐β‐amino ketones and acyl aziridines from propargyl alcohols with diverse halogen source and sulfonamides in a one‐pot fashion was investigated. This method takes place under mild conditions and low catalyst loading, is easily operated, and can be performed on a gram‐scale. Notably, catalyst Bi(OTf)3 is found to play a multi role in the cascade sequence.